Kepemimpinan Kepala Sekolah dalam Pembinaan Guru PAI di SDN Kecamatan Indrajaya Kabupaten Pidie - Mansuri Mansuri (DAYAH: Journal of Islamic Education, 2018)
One of the duties of a school principal is to guide teachers. To achieve this duty, a principal employs various approaches and styles of leadership. This study aimed to investigate the implementation of the principals’ leadership in terms of guiding the teachers of Islamic education in the elementary schools in Indrajaya, Pidie. The focuses of the study included the approaches used by the principals in guiding the teachers of Islamic education (i.e., the use of charismatic potential and authority of the principals), the styles used by the principals in guiding the teachers, and the problems faced by the principals in guiding the teachers. The study used descriptive qualitative method. The objects of the study were five elementary schools within Indrajaya. The results showed that the principals applied their charismatic potential and authority when leading the teachers of which the charimastic factor was the predominant one. The principals used participative and authoritarian leadership styles, with the former being the most preferred. Further, there were problems in guiding the teachers, including the preparation of learning instruments, learning innovations, proper assessment, teachers’ personalities, and issues during academic supervision.